Intracranial Vascular Malformations and Epilepsy - Josephson, Colin B.; Rosenow, Felix; Al-Shahi Salman, Rustam (Seminars in Neurology, 2015)
Among the spectrum of intracranial vascular malformations (IVMs), arteriovenous malformations (AVMs), and cavernous malformations (CCMs) are of particular importance for epilepsy. Seizures are a common mode of presentation for both conditions. Seizures may occur de novo or secondary to intracerebral hemorrhage. Timely imaging is thus crucial for patients with seizures and AVMs or CCMs. Patients with a first-ever AVM- or CCM-related seizure can now be considered to have epilepsy according to the International League Against Epilepsy criteria. Observational studies and case series suggest that between 45 to 78% of patients with AVM-related epilepsy and 47 to 60% of patients with CCM-related epilepsy may achieve seizure freedom through antiepileptic drugs (AEDs) alone. Invasive procedures are available although current evidence suggests that epilepsy-specific preintervention evaluations are underused. Randomized controlled trials and population-based studies have demonstrated worse short-term functional outcomes after routine intervention on unruptured AVMs or CCMs when compared with conservative management. The role of invasive therapy for IVM-related epilepsy has yielded mixed results. Case series have reported high estimates of seizure freedom although these results have not been replicated in controlled observational studies. Randomized controlled trials of immediate invasive therapy versus conservative management, in addition to usual care with AEDs and of different types of treatment and their timing, are warranted for AVMs and CCM-related epilepsy.
Keywords: arteriovenous malformations; cavernous malformations; epilepsy; antiepileptic drugs; epilepsy surgery